Investigating the Influences of Lesson Study on College EFL Adjunct Faculty's Instruction - 李多耕(To-Ken Lee) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2021)
College instructors of English as a Foreign Language (EFL) in Taiwan typically work alone when planning their teaching activities. In particular, adjunct instructors work isolated during class planning and teaching, and have fewer opportunities for professional development than fulltime instructors. This study attempts to propose a model for collaborative lesson study group for EFL adjunct instructors in a private college in Taiwan and investigates how the practices of these teacher participants can be advanced. Data collection in this study consists of qualitative inquiries, classroom observations and interview transcripts. The results indicate that the execution of a collaborative lesson study group of college adjunct faculties enhance teachers' collaboration, improve instructional wording, and forge a teachers' learning community. A collaborative study group for lesson construction helps to build a reciprocal model of learning, where teachers can help each other to identify their instructional weakness or learn from members' comments regarding demonstration lessons. However, teachers aware that to critique and question demonstration instructor might get on the nerves within group and limited common time for college adjunct faculties could diminish the effectiveness of lesson study group. Even the study of lesson construction has gained research attention, investigations of the targeted participants are so far limited to elementary and secondary school teachers. This study aims to fill the gap of previous researches regarding collaborative lesson study groups by exploring its influence on EFL adjunct faculties. The results reveal that a lesson construction study group provides EFL adjunct faculty members a systematic cycle that allows a group of teachers to streamline instructions and teaching activities through collaborative design, teaching activities design, classroom observations, and then to collaboratively refine their class lessons.